2013
DOI: 10.1186/2044-5040-3-13
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic inflammatory myopathies: pathogenic mechanisms of muscle weakness

Abstract: Idiopathic inflammatory myopathies (IIMs) are a heterogenous group of complex muscle diseases of unknown etiology. These diseases are characterized by progressive muscle weakness and damage, together with involvement of other organ systems. It is generally believed that the autoimmune response (autoreactive lymphocytes and autoantibodies) to skeletal muscle-derived antigens is responsible for the muscle fiber damage and muscle weakness in this group of disorders. Therefore, most of the current therapeutic stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 111 publications
(113 reference statements)
2
83
1
1
Order By: Relevance
“…Conversely, a Th2 cell infiltrate in DM muscle has been associated with a lower severity of disease [60]. This is due possibly to the generation of M2 macrophages by Th2 cytokines leading to tissue repair [9]. This is in contrast with the view that DM is a humorally mediated disease whereby Th2 cells would drive B cell maturation and differentiation into autoantibodyproducing plasma cells, further exacerbating microvascular damage.…”
Section: Muscle Tissuecontrasting
confidence: 52%
See 2 more Smart Citations
“…Conversely, a Th2 cell infiltrate in DM muscle has been associated with a lower severity of disease [60]. This is due possibly to the generation of M2 macrophages by Th2 cytokines leading to tissue repair [9]. This is in contrast with the view that DM is a humorally mediated disease whereby Th2 cells would drive B cell maturation and differentiation into autoantibodyproducing plasma cells, further exacerbating microvascular damage.…”
Section: Muscle Tissuecontrasting
confidence: 52%
“…The Th1 response through IFN-γ secretion leads to the induction of M1 macrophages which results in further tissue damage [9]. IMNM, previously described as an immune myopathy with a limited mononuclear cell infiltrate, has also been shown to display a strong M1/Th1 response within the muscle tissue [28].…”
Section: Muscle Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…108 Outcomes of Defective Apoptotic Cell Clearance: Autoimmunity IIM leads to disability, decreased quality of life and increased mortality. 109 Persistent inflammation with recruitment of autoreactive T cells characterizes the skeletal muscle. 110,111 Available evidence strongly supports the autoimmune underpinnings of IIM and commonly targeted autoantigens include proteins involved in DNA transcription or protein synthesis, such as the histidyl-tRNA synthase (HisRS).…”
Section: Outcomes Of Defective Apoptotic Cell Clearance: Maladaptive mentioning
confidence: 99%
“…129 Upregulation of the expression of MHC class I molecules in skeletal muscle fibers is an early feature of IIM and ectopic expression of the molecule induced ER stress response and resulted in a disease that shares several features with human IIM. 130,131 Considering that muscle injury and the associated inflammatory response represent rather common event in vivo, 109 the relative rarity of IIM indicates that a number of events must simultaneously occur to set the stage for self-sustaining autoimmunity. We have recently observed that apoptotic myoblasts are immunogenic only if appropriate adjuvants are provided in the injured/regenerating muscle.…”
Section: Figurementioning
confidence: 99%